Rancang bangun website desa lamreh sebagai media informasi - Roji Herwanda (LPPM Universitas Internasional Batam, 2023)
Lamreh is a village located in Masjid Raya sub-district, Aceh Besar district, Aceh, which has various and unique tourist objects, many local or foreign tourists who want to visit Lamreh village for holidays and some who want camping or family events. However. lack of information about this village so that the village is less visited by local and foreign tourists. And the location is also far from urban banda aceh. So Lamreh village really needs a website to provide complete information. This application contains a design for a village information system including village profiles, tourist information, and information about Lamreh village. This study uses the waterfall method. The research stages include data collection, analysis, design, coding, implementation testing.